Uric acid is associated with increased risk of myocardial infarction: results from NHANES 2009-2018 and bidirectional two-sample Mendelian randomization analysis - Deng, Ting; Liu, Xiaoying (Frontiers in Endocrinology, 2024)
Although a growing number of studies have shown that elevated uric acid (UA) levels are associated with multiple cardiovascular risk factors and progression of coronary artery disease, the causal relationship between UA and the occurrence of myocardial infarction (MI) remains uncertain. The aim of this study was to investigate the relationship between UA and the risk of MI.We screened 23,080 patients in the National Health and Nutrition Examination Survey (NHANES) database for 2009-2018 and explored the association between UA and MI risk using multivariate logistic regression model. In addition, a two-way two-sample Mendelian randomization (TSMR) analysis was performed to examine the causal relationship of UA on MI, and inverse varianceweighted (IVW) results were used as the primary outcome in this study. Sensitivity analysis and horizontal multiple validity test were also performed to verify the reliability of the results.After multivariable adjustment, individuals with the severe elevation of UA levels have a significantly increased risk of MI (OR=2.843, 95%CI: 1.296-6.237, P=0.010). In TSMR analysis, the IVW method demonstrated a significant association between UA and increased risk of MI (OR=1.333, 95%CI: 1.079-1.647, P=0.008). Results from the MR-Egger intercept test, Cochran's Q test, and MR-PRESSO test all suggest the reliability of the IVW analysis. Reverse TSMR analysis did not indicate a causal relationship between genetic susceptibility to MI and UA levels (IVW: OR=1.001, 95%CI: 0.989-1.012, P=0.922).Based on cross-sectional study and Mendelian randomization analysis, it has been demonstrated that UA is an independent risk factor for MI. Elevated levels of UA increase the risk of MI, particularly in cases of severe elevation.